Cerebral angiitis associated with subarachnoid hemorrhage in Castleman's disease: report of two cases. Issue 1 (December 2016) - Tanaka, Jun; Fujita, Atsushi; Hosoda, Kohkichi; Kohmura, Eiji
Abstract Background Multicentric Castleman's disease (MCD) is characterized by a systemic lymphoproliferative disorder affecting systemic lymph nodes. Cerebrovascular involvements have rarely been reported, and to our knowledge, cerebral angiitis causing subarachnoid hemorrhage (SAH) in patients with Multicentric Castleman's disease (MCD) has not been previously described. Case presentation We identified two cases of MCD with SAH who were receiving immunosuppressive therapy with low dose prednisolone. Both patients presented with sudden-onset headache and were diagnosed with cortical SAH in the sulci by a computed tomography scan. Digital subtraction angiography showed segmental stenosis in the peripheral area of the middle cerebral artery. In both cases, cerebral angiitis causing SAH induced by a systemic inflammatory condition and elevated levels of interleukin (IL) -6 were suspected and resolved over a period of several months. Conclusion Our cases highlight the clinical diversity of the potential causes of cerebral angiitis and expand the association of MCD and cortical SAH; however, cortical SAH patients have a more favorable outcome than aneurysmal SAH patients.